Kesepakatan Penyelesaian Kepemilikan Pulau Sipadan dan Ligitan Prespektif Mahkamah Internasional - Aulia Arifany Safitri; Adinda Pra Septia Sheila; Ruth Anastasya Sandy Simanjuntak Tasya (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2024)
A sovereign state is one that should know its territorial boundaries with certainty. Where as a result of the lack of the absence of certainty of territorial boundaries based on legal aspects, Indonesia and Malaysia were forced to accept the case of case, namely the case of Sipadan and Ligitan Islands. The settlement of cases that could not be resolved through negotiations, led the two countries to agree to settle the case through the International Court of Justice. The verdict on the settlement of the case declared Malaysia as the country that has the right to control the island. However, Indonesia's agreement to to settle the case through the International Court of Justice is not wrong, which is in accordance with the principles of world peace. Likewise, the decision of the International Court of Justice which is in accordance with legal procedures and has been supported by the knowledge/experience possessed by/of the judges. So it can be said that the agreement between the two countries that created the transfer of the islands of Sipadan and Ligitan was not a gift to Malaysia. Discussion the author's goal, because according to the author this study is an important study and needs to be discussed as a material is an important study and needs to be discussed as a new analytical study that is different from other authors' studies. So that in writing, the author uses a normative juridical method, which uses an analytical approach, legal concepts and regulation laws.